THE ARCHITECTS’ AND LANDSCAPE ARCHITECTS’ VIEWS ON THE DESIGN AND PLANNING OF THE HOSPITAL COURTYARD GARDENS (HCG) IN MALAYSIA - Mat Idris, Madihah; Sibley, Magda; Hadjri, Karim (PLANNING MALAYSIA, 2022)
This paper presents the architects' and landscape architects' point of views on their original design intentions in designing and planning hospital courtyard gardens (HCGs) in Malaysia. Following a field observation, a semi-structured interview with two architects and two landscape architects was conducted. Additionally, the architectural design briefs for three selected Malaysian hospitals were obtained as secondary data for this study. The results revealed that the intended common design pointed out by the architects includes: i) Daylighting strategy; ii) Ventilation strategy; iii) Access to nature; and iv) Point of orientation. Landscape architects, on the other hand, are concerned with: i) Forest-like garden concept; ii) Natural and organic form instead of aesthetic appearance; iii) An escape place for relieving stress and; iv) A hang-out space for socialisation. This paper contributes to the understanding of how designers would think and determine the architectural plan and landscape design in achieving an optimal HCG design to meet the needs of the intended users.